2020
DOI: 10.1016/j.jhep.2020.04.006
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Abnormal liver function tests

Abstract: Abnormal liver function tests in patients with COVID-19Liver injury associated with use of drugs in patients with COVID-19

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

93
1,268
11
50

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 921 publications
(1,422 citation statements)
references
References 33 publications
93
1,268
11
50
Order By: Relevance
“…Among a variety of recent publications about COVID-19, accumulated evidence suggests that SARS-CoV-2 infections might cause multiple and systemic injuries, including acute renal failure, myocardial dysfunction, and acute liver injury 20,24,25 . Additionally, there are recent studies analyzing COVID-19 patients in detail with respect to liver enzymes, such as ALT and AST 20,26 . The underlying mechanism of elevated liver enzymes in COVID-19 patients remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Among a variety of recent publications about COVID-19, accumulated evidence suggests that SARS-CoV-2 infections might cause multiple and systemic injuries, including acute renal failure, myocardial dysfunction, and acute liver injury 20,24,25 . Additionally, there are recent studies analyzing COVID-19 patients in detail with respect to liver enzymes, such as ALT and AST 20,26 . The underlying mechanism of elevated liver enzymes in COVID-19 patients remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The derangement of liver function tests at presentations has been reported in up to 50% of patients without liver disease [21]. The exact signi cance of the rise in transaminases and its relation to outcomes is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Some studied showed that about majority of COVID-19 patients had received nonsteroidal anti-in ammatory drugs, antibiotics and antiviral agents (e.g., acetaminophen, moxi oxacin, oseltamivir, arbidol, lopinavir/ritonavir, etc), all of above drugs had explicit liver injury effect, such as type 2 and type 4, however, it is even di cult to evaluate exact liver damage particularly in combination therapy. 2,3,11,12,14,22 Fourth, underlying of chronic liver disease. Guan et al found that non-severe patients with COVID-19, even though they have basic liver diseases (such as viral hepatitis, etc.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Studies have con rmed that SARS-CoV-2 enters cells primarily through angiotensin converting enzyme2 (ACE2), the high expression of ACE2 in alveolar type II cells makes the lung become the main target organ. 9,10 A number of existing clinical studies showed that some patients with COVID-19 had different degrees of liver dysfunction [11][12][13][14][15][16] and the liver biopsy from a dead COVID-19 case showed moderate microvascular steatosis and mild lobular activity in addition to severe lung injury. 17 The objective of this retrospective study was to explored the pattern of liver dysfunction, risk factors and outcomes in patients with COVID-19, so as to provide reference for clinical decision-making.…”
Section: Introductionmentioning
confidence: 99%